Dose-dependent role of AMH and AMHR2 signaling in male differentiation and regulation of sex determination in Spotted knifejaw (Oplegnathus punctatus) with X1X1X2X2/X1X2Y chromosome system - Haixia Zhao; Jun Li; Zhizhong Xiao; Yongshuang Xiao (Cell Communication and Signaling)
Abstract Sex determination mechanisms vary significantly across different chromosomal systems and evolutionary contexts. Nonetheless, the regulatory framework governing the multi-sex chromosome system (X1X1X2X2/X1X2Y) remains enigmatic. Through an examination of sex-related genes (dmrt1, hsd11b2, amh, sox9a, sox9b, foxl2, cyp19a), hormonal influences (E2, 11-KT), and histological analyses of gonadal development, we demonstrate that the critical period for sexual differentiation occurs between 35 to 60 days post-hatching (dph). Our multi-omics analysis identified amhr2 as a candidate sex-determining gene, revealing that the males possess three distinct amhr2 transcripts (amhr2ay, amhr2by, amhr2cy), whereas females express only one (amhr2a). In situ hybridization assays demonstrated that amhr2 is predominantly localized to primary spermatocyte and Sertoli cells of male testes. Notably, the specific mRNA expression of amhr2 is significantly enriched in amhr2cy, whose extracellular domain exhibits the highest binding affinity for Amh protein, with sexual expression differences manifesting as early as 5 dph. The outcomes of amhr2 interference (RNAi) experiments indicate that amhr2 knockdown leads to a reduction in the expression of male-related gene (dmrt1, amh, sox9a, sox9b), androgen synthesis genes (hsd11b2, cyp11a), and female-related genes (wnt4, foxl2, cyp19a, cyp19b). Conversely, overexpression of amhr2 yielded contrasting results. Our research supports the role of amhr2 as a pivotal candidate sex-determining gene. Furthermore, the dosage effect of amhr2, reflected in transcript abundance, mRNA expression levels, and binding efficacy, serves as a fundamental mechanism driving male differentiation and regulatory processes in Spotted knifejaw.